TQM and firms performance: An EFQM excellence model research based survey - María Leticia Santos-Vijande; Luis I. Alvarez-Gonzalez (International Journal of Business Science & Applied Management (IJBSAM), 2007)
The purpose of this article is to develop an instrument for measuring TQM implementation following the European Foundation for Quality Management Excellence Model and to provide empirical evidence on the relationship between management practices and measures of business performance in the model. To this end, the study employs survey data collected from Spanish manufacturing and service firms. Confirmatory factor analysis is used to test the psychometric properties of the measurement scales and the hypothesized relationships between total quality management practices and organizational performance are examined using structural equation modeling. The findings of the research indicate that the adoption of the TQM practices suggested in the EFQM Excellence Model allows firms to outperform their competitors in the results criteria included in the Model. Therefore, this paper provides a valuable benchmarking data for firms as it substantiates the EFQM Enabler's contribution to the attainment of competitive advantage.
Keywords: 650; total quality management; business performance; competitive advantage; EFQM excellence model; Spain